2020
DOI: 10.1002/brb3.1762
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between SDB and short‐term outcome in Finnish ischemic stroke patients

Abstract: Sleep-disordered breathing (SDB) is frequent among ischemic stroke and TIA patients and several studies have estimated the prevalence between 50% and 70% depending on the definition (Bassetti &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…We could not find other variables related to worse short-term functional outcome. In our previous study, higher disability and need of rehabilitation and longer hospitalization time were seen in OSA patients (Haula et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We could not find other variables related to worse short-term functional outcome. In our previous study, higher disability and need of rehabilitation and longer hospitalization time were seen in OSA patients (Haula et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…In our previous study, higher disability and need of rehabilitation and longer hospitalization time were seen in OSA patients. (Haula et al, 2020) Because the higher proportion of moderate-to-severe OSA in WUS patients we hypothesized we could find significant difference in the other two outcome measures. Reason for insignificant difference can be the low number of WUS patients with higher disability and even smaller number of those with combination of OSA and WUS in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, a Finnish study reported positive associations between NIHSS scores at admission and discharge with SDB, mirroring the outcomes observed in our cohort. 17 In our study, minor strokes dominated the cohort, with a median NIHSS score of 2. [1][2][3][4] Good compliance with overnight PSG completion in minor stroke might explain this finding.…”
Section: Discussionmentioning
confidence: 63%